Advanced cooling heat pump and desalination employing functional UiO-66 (Zr) metal-organic frameworks - Han, Bo (2022)
This article presents a comprehensive study of UiO-66 (Zr) based metal-organic frameworks (MOFs) plus water systems for various adsorption assisted heat transformation (AAHT) applications such as cooling, heat pump and desalination. The paper at first deals with the evaluation of water adsorption characteristics on the parent and pyridine, amino, and hydroxyl functional groups based UiO-66 (Zr) MOFs. The experiments are carried on for temperatures varying from 25 to 80 °C and pressures up to the saturated conditions. Based on experimentally confirmed isotherms and kinetics data, the adsorption assisted heat transformation systems are modelled and simulated. Hence the thermal storage system is also modelled with the addition of both heat and mass recoveries. Finally, the performances of adsorption cooling/heat pump/desalination are calculated with respect to various cycle time, heating source and cooling load temperatures. Hence, hydroxyl (–OH) and amino (–NH2) functional group UiO-66 MOFs improves water transfer from 0.05 kg/kg to 0.32 kg/kg. On the other hand, OH-UiO-66 (Zr) + water system shows the faster kinetics and –NH2 group also provides relatively higher Δq (uptake-offtake difference) per adsorption-desorption cycle. The functional groups enhance the hydrophilic behavior of the parent UiO-66 MOFs in the low pressure zone, which improves overall efficiency. The SCP (specific cooling power) enhances from to 0.36 kW/kg to 0.84 kW/kg and the SHP (specific heating power) increases from 0.9 kW/kg to 1.48 kW/kg. In addition, the SDWP (specific daily water production) improves from 24 to 40 m3 of purified water per tonne of MOFs-adsorbent per day. These results confirm that functionalized UiO-66 (Zr) MOFs are competent candidates for adsorption cooling, heat pump and desalination applications.